2022
DOI: 10.1111/mcn.13367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of integrated nutrition‐sensitive and nutrition‐specific intervention package on maternal malnutrition among pregnant women in Rwanda

Abstract: Maternal undernutrition remains a major public health concern in Rwanda despite significant gains and progress. An integration of nutrition‐specific and nutrition‐sensitive interventions was implemented in five districts of Rwanda to improve maternal and child nutrition. The package included nutrition education and counselling, promotion of agricultural productivity, promotion of financial literacy/economic resilience and provision of Water, Hygiene and Sanitation services. However, there is limited evidence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
3
2
Order By: Relevance
“…Studies by Michael Habtu et al [32], Sunita Taneja et al [7], Melesse Kuma et al [33] revealed elevated haemoglobin levels among women in the intervention group, findings that our study was unable to replicate due to the constraints related to equipment and supplies.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Studies by Michael Habtu et al [32], Sunita Taneja et al [7], Melesse Kuma et al [33] revealed elevated haemoglobin levels among women in the intervention group, findings that our study was unable to replicate due to the constraints related to equipment and supplies.…”
Section: Discussioncontrasting
confidence: 58%
“…However, it is worth noting that the effect of iron/folic acid supplementation on haemoglobin levels in both settings could not be assessed in both settings due to lack of equipment and supplies. Studies by Michael Habtu et al [32], Sunita Taneja et al [7], Melesse Kuma et al [33] revealed elevated haemoglobin levels among women in the intervention group, findings that our study was unable to replicate due to the constraints related to equipment and supplies.…”
Section: Discussioncontrasting
confidence: 55%
“…All these improved knowledge and skills; in addition, a changed positive mindset regarding nutrition and women empowerment could have affected on the perceived improved nutritional status by addressing both immediate and underlying causes of malnutrition as highly expressed by many of the key informants and FGDs participants in the study. This is supported by quasi-experimental studies conducted by the same authors, which found that the Gikuriro intervention was associated with a significant reduction of low birth weight and maternal undernutrition [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 77%
“…Recent quantitative studies have been performed to evaluate the effect of the Gikuriro program on maternal nutritional status and birth weight. Both postprogram quasi-experiments revealed that the intervention led to significant reduction of low birth weight and maternal undernutrition [ 12 , 13 ]. The main success factor having been attributed to the integration of nutrition-specific and nutrition-sensitive intervention package.…”
Section: Introductionmentioning
confidence: 99%
“…These follow a pathway to enhance calorie consumption and micronutrient intakes that, in turn, affect maternal health outcomes (18). Together, nutrition-speci c interventions such as counselling -behavioural change interventions and education/ awareness and nutrition-sensitive interventions -cash incentives have compounding effect on the maternal dietary diversity compared to a speci c intervention (19). However, pathways determining the change across population groups have been a contesting topic.…”
Section: Introductionmentioning
confidence: 99%